2016
DOI: 10.1007/s00259-016-3544-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [11C]Lu AE92686 as a PET radioligand for phosphodiesterase 10A in the nonhuman primate brain

Abstract: Purpose[11C]Lu AE92686 is a positron emission tomography (PET) radioligand that has recently been validated for examining phosphodiesterase 10A (PDE10A) in the human striatum. [11C]Lu AE92686 has high affinity for PDE10A (IC 50 = 0.39 nM) and may also be suitable for examination of the substantia nigra, a region with low density of PDE10A. Here, we report characterization of regional [11C]Lu AE92686 binding to PDE10A in the nonhuman primate (NHP) brain.MethodsA total of 11 PET measurements, seven baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…In 2017, Yang et al [ 160 ] reported on the in vivo evaluation of another already known PDE10A-specific radioligand, [ 11 C] LuAE92686 [ 124 , 125 , 126 ] ([ 11 C] 32 , see Figure 6 ), in non-human primates. The suitability of [ 11 C] 32 for PET imaging and quantification of PDE10A in the target region striatum has previously been proven in non-human primates and humans [ 1 , 124 ].…”
Section: Pde10a Radioligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2017, Yang et al [ 160 ] reported on the in vivo evaluation of another already known PDE10A-specific radioligand, [ 11 C] LuAE92686 [ 124 , 125 , 126 ] ([ 11 C] 32 , see Figure 6 ), in non-human primates. The suitability of [ 11 C] 32 for PET imaging and quantification of PDE10A in the target region striatum has previously been proven in non-human primates and humans [ 1 , 124 ].…”
Section: Pde10a Radioligandsmentioning
confidence: 99%
“…The suitability of [ 11 C] 32 for PET imaging and quantification of PDE10A in the target region striatum has previously been proven in non-human primates and humans [ 1 , 124 ]. The aim of the current PET study was to further characterize the binding of [ 11 C] 32 to PDE10A regarding specificity and kinetics and to examine whether [ 11 C] 32 is suitable to accurately quantify PDE10A levels in the substantia nigra where this enzyme is exclusively expressed in nerve fibers and terminals [ 101 , 160 ]. The substantia nigra is a key nucleus in relation to the basal ganglia and thus, regional dysfunction of PDE10A is suggested to be associated with the pathophysiology of neuropsychiatric disorders like schizophrenia [ 160 ].…”
Section: Pde10a Radioligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the identified metabolite is not expected to bind to PDE10A and authors of human studies claim this does not impact the quantification of PDE10A with 18 F-JNJ42259152 [130]. 11 C-Lu AE92686 underwent fast metabolism in NHP, with slow increase in cerebellum V T observed throughout the scan, indicating a brain-penetrating metabolite may be present in small quantities [141]. The cerebellum V T increase over time has not yet been reported in human, preventing the assessment of the possibility of brain-penetrating metabolite accumulation.…”
mentioning
confidence: 99%